RESEARCH OF BRIDGE STRUCTURE VIBRATION CHARACTERISTICS - Babak, V.P.; Filonenko, S.F.; Kalita, V.M.; Kornienko-Miftakhova, I.K. (Proceedings of National Aviation University (archive), 2005)
Bridge structure test results with using different types of dynamic force have been considered. It has been shown, that the developed technique of registering and processing vibration signals allows obtaining thin spectrum structure. The analysis of its change that is defined by the type of structure loading applied has been carried out. Key parameters of the vibration signals registered have been defined.